L’apprentissage informel au service de l’enseignement de la littérature et de la culture à la philologie française - Grabowska, Monika; Sadkowska-Fidala, Agata (2023)
The aim of the present study is to examine the extent to which French philology students' informal learning – in the area of multimodal literacies and leisure activities – reinforces the gains in French literature and French history and culture courses through creative mediation. We report on an experiment conducted in the years 2020-2022 in five online courses at the French Philology department of the University of Wrocław during the Covid-19 pandemic. In these courses, students were expected to personally mediate the texts or content studied in class and present them on a group Facebook site. The students' projects are classified according to two criteria (intersemiotic and intrasemiotic mediation; mediation of form and content) and prove that the involvement of informally acquired knowledge and skills not only developed the students' creativity, but also promoted interpretative processes by anchoring the formal learning of the course in personal experience.
Keywords: informal learning; teaching literature and culture; French as a foreign language; mediation; creativity